Răspunsuri

2014-03-19T17:39:44+02:00
3x(3x-2)=6-7    3x(3x-2)=--1   3x ori 3x-2=minus 1   3x ori 3x =2+1   3x la puterea a 2=3  3x la a 2a-3=0   3x la a 2a-radical din 3=0      (1x-3)(1x+3)=0    1x-3=0    1x=3   x=3:1   x=3        1x+3=0    1x=--3     x=--3:1  x =--3
S={3;--3}
2014-03-19T17:46:50+02:00
3x(3x-2)=6-7    3x(3x-2)=--1   3x ori 3x-2=minus 1   3x ori 3x =2+1   3x la puterea a 2=3  3x la a 2a-3=0   3x la a 2a-radical din 3=0      (1x-3)(1x+3)=0    1x-3=0    1x=3   x=3:1   x=3        1x+3=0    1x=--3     x=--3:1  x =--3
S={3;--3}